COVID-19, the oil price slump and food security in low-income countries - Maximilian Heigermoser; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2020)
The shutdown measures implemented to fight the Covid-19 pandemic resulted in a historic drop in crude oil prices, which implies existential challenges to countries depending on energy exports. The three largest crude oil exporters in Africa (Algeria, Angola and Nigeria) are - like numerous other raw material exporters worldwide - facing devaluing currencies and dwindling currency reserves. As food security in these states largely depends on imports of wheat and rice, domestic food prices are expected to rise due to the currency depreciation. This puts further pressure on populations with already low incomes, while local shutdowns and reduced economic activity lead to additional income losses. Recent panic buying and (temporary) export restrictions on international grain markets further exacerbate the situation. Not least due to currently ample grain stocks, such measures are not to be recommended. Instead, solidarity amongst nations, taking the form of emergency aid such as debt relief, food deliveries and medical aid, is required more urgently than ever. Furthermore, it is advisable to ease bureaucratic and tariff trade barriers to facilitate international trade. Demands for greater autarchy and de-globalisation should be avoided in the current precarious situation. – – Die "Shutdown"-Maßnahmen zur Bekämpfung der Covid-19-Pandemie haben zu einem Preisverfall auf den Rohöl- und Energiemärkten geführt, der erdölexportabhängige Staaten vor existenzielle Herausforderungen stellt. Die drei größten Rohölexporteure Afrikas (Algerien, Angola und Nigeria) sind dadurch - wie zahlreiche weitere Rohwarenexporteure weltweit - mit abwertenden Währungen bzw. schwindenden Währungsreserven konfrontiert. Da die Ernährungssicherheit genannter Staaten maßgeblich von Weizen- und Reisimporten abhängt, ist zu erwarten, dass die Währungsabwertungen zu steigenden Lebensmittelpreisen im Inland führen werden. Dies erhöht den finanziellen Druck auf Menschen mit ohnehin niedrigen Einkommen, die durch lokale Shutdown-Maßnahmen und verminderte wirtschaftliche Aktivität zusätzlich von Einkommensverlusten betroffen sind. Die jüngsten Panikkäufe und (kurzzeitigen) Exportbeschränkungen auf internationalen Getreidemärkten verschärfen die Situation. Auch angesichts gegenwärtig ausreichender Lagerbestände kann hiervor nun dringend abgeraten werden. Gefordert ist nun vielmehr die Solidarität der Staatengemeinschaft in Form von Soforthilfen, wie etwa Schuldenerlässe, Nahrungsmittellieferungen und medizinische Hilfen. Gleichzeitig sind tarifäre und bürokratische Handelshemmnisse im internationalen Warenaustausch kurzfristig abzubauen. Vor Autarkierufen kann in einer solch prekären Versorgungssituation nur gewarnt werden.
urn:nbn:de:gbv:3:2-123075
Keywords: 330; Shutdown; Ölpreis; Ernährungssicherung; Entwicklungsländer; Afrika